2016
DOI: 10.2169/internalmedicine.55.6003
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy and Palliative Care Prolongs the Survival of Hepatocellular Carcinoma Patients with Bone Metastases

Abstract: Objective In recent years, an increase has been observed in the incidence of bone metastases from hepatocellular carcinoma (HCC). In 2007, our institution established a team approach, which includes the provision of palliative care. In the present study we evaluate the effects of palliative care on the prognosis of HCC patients with bone metastases. Methods The subjects included 44 patients with bone metastases who were treated with radiotherapy be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
(35 reference statements)
0
13
0
2
Order By: Relevance
“…In addition, EBRT for lung metastases resulted in response rates from 65% to 75% while symptom relief was achieved in 90% of symptomatic patients (496500). EBRT is reported to relieve pain in 75% to 99% of patients with symptomatic bone metastases (501502503504505506507). Moreover, in a previous study, EBRT for spinal cord compression from vertebral metastases is reported to prevent neurologic dysfunction in 63% to 83% of patients (508509510).…”
Section: External-beam Radiation Therapymentioning
confidence: 99%
“…In addition, EBRT for lung metastases resulted in response rates from 65% to 75% while symptom relief was achieved in 90% of symptomatic patients (496500). EBRT is reported to relieve pain in 75% to 99% of patients with symptomatic bone metastases (501502503504505506507). Moreover, in a previous study, EBRT for spinal cord compression from vertebral metastases is reported to prevent neurologic dysfunction in 63% to 83% of patients (508509510).…”
Section: External-beam Radiation Therapymentioning
confidence: 99%
“…[ 25 ] Palliative care, including radiotherapy and adequate analgesics improves the prognosis and survival time of HCC patients with metastatic bone tumors by improving their general conditions. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos artigos trazem primeiramente como o tratamento do CHC é realizado (Miguet et al, 2019;Herneaz & Hashem, 2018;Siddique et al, 2017;Sakaguchi et al, 2016;Taddei, 2013;Hong et al, 2006;Târcoveanu, 2005;Läuffer et al, 1999) necessários são: patologista, radioterapeuta, médico de medicina nuclear e psiquiatra. (Miguet et al, 2019;Herneaz & Hashem, 2018;Siddique et al, 2017).…”
Section: Fonte: Própriaunclassified
“…Tal atitude melhora a qualidade de vida e da morte, especialmente para os que estão em estado terminal, fornecendo um cuidado holístico tanto para a pessoa o como para sua família (Cheng et al, 2013). É importante mencionar que os cuidados paliativos quando realizados precocemente, melhoram a qualidade de vida, bem como do humor e maior aumenta a sobrevida do indivíduo com CHC (Miguet et al, 2019;Herneaz & Hashem, 2018;Sakaguchi et al, 2016;Cheng et al, 2013).…”
Section: Fonte: Própriaunclassified